Implementation of fundamental movement learning gymnastics in elementary schools - Herman Chaniago; Wahyuningtyas Puspitorini; Yafi Velyan Mahyudi (Journal Of Sport Education (JOPE), 2024)
(English)This research aims to study how students learn basic floor exercise movements in elementary school and the impact on physical and cognitive growth. The results of this research will provide guidelines for learning gymnastics in elementary schools and increase awareness of the importance of fun and interactive learning methods. The research method used in this action research is the Kemmis and McTaggart model. The research subjects were students from the second grade of elementary school aged between 8-9 years and totaling 27 children, consisting of 17 girls and 12 boys. The research instrument was an observation sheet related to students' responses during learning and basic gymnastics movement skills. The balance indicator obtained the highest average score, namely 84, twisting movement 79, rolling movement 72, and flexibility 75. From the results of the assessment, the average met the minimum criteria for student completeness in physical education learning. Meanwhile, the difference in assessments from cycle I and cycle II obtained a result of 2.868 which was greater than t0 2.755 and α (0.05). This research confirms that the implementation of basic gymnastics movements in elementary school students is effective in improving balance, coordination, and flexibility. It has a positive impact on student's physical development and should be integrated into the primary school sports curriculum. Research also confirms the important role of physical health in preparing children physically.(Indonesian)Tujuan penelitian ini untuk mempelajari bagaimana siswa belajar gerak dasar gymnasticdi sekolah dasar dan dampak pada pertumbuhan fisik dan kognitif. Hasil penelitian ini akan memberikan pedoman pembelajaran senam di sekolah dasar dan meningkatkan kesadaran akan pentingnya metode pembelajaran yang menyenangkan dan interaktif. Metode penelitian yang digunakan dalam penelitian tindakan ini adalah model Kemmis dan Mc Taggart. Subyek penelitian adalah siswa dari kelas dua SD yang berusia antara 8-9 tahun dan berjumlah 27 anak, terdiri dari 17 perempuan dan 12 laki-laki. Pengambilan sampel dengan purposive sampling yaitu menetapkan usia pada level 1 gymnastic. Instrumen penelitian berupa lembar observasi yang terkait dengan respon siswa selama pembelajaran dan tes keterampilan gerak dasar senam. Pada indicator keseimbangan memperoleh nilai rata-rata paling tinggi yaitu 84, gerakan memutar 79, gerakan berguling 72 dan kelenturan 75. Dari hasil penilaian tersebut rata-rata sudah memenuhi kriteria ketuntasan minimum siswa dalam pembelajran pendidikan jasmani. Sedangkan perbedaan penilaian dari siklus I dan siklus II diperoleh hasil 2,868 lebih besar dari t0 2,755 dan α (0,05). Penelitian ini mengkonfirmasi bahwa implementasi gerak dasar gymnastic pada siswa sekolah dasar efektif dalam meningkatkan keseimbangan, koordinasi, dan fleksibilitas. Ini memiliki dampak positif pada perkembangan fisik siswa dan sebaiknya diintegrasikan dalam kurikulum olahraga sekolah dasar. Penelitian juga mengkonfirmasi peran penting kesehatan fisik atau untuk mempersiapkan fisik bagi anak-anak.Copyright © The Author (s) 2024Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.